Anaceting Mobile Health Application: An Innovative Digital Solution for Early Stunting Detection in Indonesian Children - Riski Novera Yenita; Viana Anggraini; Afdhal Islami; Khaidir Ansyari (Jurnal Penelitian Pendidikan IPA, 2025)
Stunting is a complicated public health problem in Indonesia, with a countrywide rate of 21.5% in 2023. Puskesmas Rejosari in Pekanbaru City had the most stunting instances, with 50 out of 239. This shows that new ways are needed to find stunting cases early and teach people in the community about it. The goal of this study is to create the ANACETING (Stunting Prevention Information Application) Android app as a digital tool for finding stunting in toddlers early. The study is at the fourth stage of the Research and Development (R&D) approach and includes 30 mothers of toddlers as test subjects.A panel of media and material experts conducted validation using a structured questionnaire with 22 items on a Likert scale instrument. The app contains tools for measuring growth, interactive educational content, guidelines for supplementary feeding, immunization schedules, and a space for individuals in the community to chat about topics. The media expert gave it a score of 4.00 (in the "Feasible" category), while the content expert gave it a score of 4.00 with a content validity grade of 0.80. The user trials showed a satisfaction score of 4.20 and a System Usability Scale score of 82.5 (category "Very Feasible"). The job completion rate was 96%, and the user retention rate was 87%. The ANACETING software has shown to be a good digital learning tool since it is easy to use, works on a lot of Android devices, and can be used offline. Women may learn more about stunting and support community-level initiatives to stop it by using the app. This research helps Indonesia's digital health technology expand by employing a strategy that may work in any part of the nation.